Discussion of the Time Series Behavior of Earnings - Kaplan, Robert S. (Journal of Accounting Research, 1970)
My general impression of Professor Beaver's paper is that it is an excellent job of empirical analysis. However, I found as I was reading it that I was unsure as to the motivation and implication of the models being analyzed. At the outset, a number of empirical studies are mentioned that each use accounting earnings in some manner. Beaver concludes that the findings of these studies may be conflicting or paradoxical. The motivation for his study would have been much clearer had the conflicting or paradoxical conclusions he was referring to been specifically mentioned along with how the research described in the study was going to resolve these issues. We must be content, though, with statements that more knowledge of the accounting earnings process is required without specific indication of how this additional knowledge is going to be used. The tone of the opening and closing remarks in the paper suggest that Beaver had specific reasons for undertaking the investigation that was reported here and the contribution of the paper would have been clearer if he had spent more time in explaining the implications of his hypothesized models on existing valuation, dividend, and portfolio models. A primary conclusion of the empirical research is that the accounting earnings stream may be viewed as smoothing the underlying, more erratic, series of economic events that a firm experiences. I find this conclusion unsurprising so that the study serves mainly to validate prior beliefs, which is still, however, a useful goal. The particular type of smoothing discussed (allocating an equal share of unexpected return to some number of future periods) is admittedly only a first approximation to be refined in later analysis. Beaver feels that depreciation policy is a principal cause of such income smoothing and proposes to test this hypothesis in future research. I would